The role of prosody, semantic and syntactic structures in defining communicative aim of utterance - Н. Р. Григорян; Є. М. Музя (Записки з романо-германської філології, 2015)
The article deals with the problems connected with the functioning of American prosody in business discourse. Prosodic, lexical and syntactic affective means are defined in convincing monologues. Frequency of key words and their accentuation attract the listeners' attention to that part of utterance, which is accentuated according to the goals of both the speaker and communicative situation. The relevance of the chosen topic is dictated by the process of globalization, the development of business contacts and cooperation in the field of business, and in this regard, the growing need for more in-depth and detailed study of the conditions of successful communication. The subject of this study is prosodic characteristics in their relation to the lexical composition of words and a pragmatic objective of impact in monological discourse. The material of research is based on the monological part of interviews of 10 American businessmen in Audiocourse "Conversations with the greatest world leaders of business network", publishing house "Upline" 1996. The total duration of the experimental material was 5 hours. Monological utterances of 3 men and 3 women were selected for the audit analysis. Thus, the narrow corpus of study lasts 45 minutes. As the minimal unit of analysis in this study we consider the intonation group defined as a speech segment, limited on two sides by pauses and having a prosodic integrity and completeness. The purpose of this study is to identify the prosodic speech means that contribute to the realization of the communicative strategies aimed at attracting new "leaders" for business expansion. Based on the purpose of the study, this paper addresses the following tasks: - To identify the relative frequency of key words relating to the frame 'success - business - leaders" and the syntactic and lexical means of their foregrounding in discourse; - To conduct an audit analysis of melodic configurations of quasi-spontaneous monological speech employing the system of phonetic marking. The problem of prosodic realization of the function of impact has been paid much attention. However, in our opinion, this issue requires a further careful study, as the realization of function of impact involves linguistic means. Along with prosodic means we should talk about the lexical and syntactic means of foregrounding the relevant information in discourse, i.e. an integrated approach when dealing with this phenomenon.